LANGUAGE STYLE AND PRESERVING LOCAL IDENTITY IN WAYANG BANYUMAS THROUGH VOCATIONAL HIGH SCHOOL STUDENTS’ PERFORMANCE - Dian Adiarti (Jurnal Lingua Idea, 2019)
This research is aimed at identifying language style used in Wayang Banyumas and describing the local wisdom reflected in the students’ performance. Local wisdom or also known as local genius may be defined as the sum of the cultural characteristics which the vast majority of a people have in common as a result of their experiences in early life. This is a descriptive qualitative research since it comes up with the identification of language style used in Wayang Banyumas. The primary data were collected from Wayang Banyumas performed by the students of State Vocational High School (SMKN) 3 Banyumas; there were five performances entitled Bilawa Rangsang, Jarasanda Lena, Abiyasa Sayembara, Gendreh Kencana, and Wisangeni Krama respectively. To complete the data, the secondary data were gained from documentation and interview with some key informants who are expert of Wayang Banyumas for enriching the data description. The results reveal several language styles used in Wayang Banyumas dominated by the finding of figurative language and phonological features. Figurative languages found are: metaphor, simile, and hyperbole while the phonological features collected are assonance (purwakanti swara) and alliteration (purwakanti sastra) which belong to repetition of vowel or consonant sounds in a sequence of nearby words. Moreover, socio-cultural values and moral messages are also reflected in wayang performance. It taught the ideal figure of leader, the excellence of deliberation or musyawarah, peaceful act, and honesty.